Apple Endophytic fungi and their antagonism against apple scab disease - Ebrahimi, Leila; Hatami Rad, Sepideh; Etebarian, Hassan Reza (Frontiers in Microbiology, 2022)
Endophytic fungi are microorganisms with the ability to colonize plants for the entire or at least a significant part of their life cycle asymptomatically, establishing a plant-fungus association inside the living plant tissue. They play an important role in balancing ecosystems, as well as benefiting host through increasing plant growth, and protecting the host plants from abiotic and biotic stresses using various strategies. In the present study, endophytic fungi were isolated from wild and endemic apple cultivars, followed by characterizing their antifungal effect against Venturia inaequalis. To characterize the endophytic fungi, 417 fungal strains were separated from 210 healthy fruit, leaf, and branch samples collected from the north of Iran. Among the purified fungal isolates, 33 fungal genera were identified based on the morphological characteristics, of which 38 species were detected according to the morphological features and molecular data of ITS, tef-1α, and gapdh genomic regions (related to the genus). The results represented that most of the endophytic fungi belonged to Ascomycota (67.8%), 31.4% of isolates were mycelia sterilia, while the others were Basidiomycota (0.48%) and Mucoromycota (0.24%). Additionally, Alternaria, Cladosporium, and Nigrospora were determined as the dominant genera. The antifungal properties of the identified isolates were evaluated against V. inaequalis in vitro to determine the release of secondary metabolites, Volatile Organic Compounds (VOCs), chitinase, and cellulase as antifungal mechanisms, as well as producing phosphate solubilisation as growth-promoting effect. Based on the results of secondary metabolite and VOC tests, the six isolates of Acremonium sclerotigenum GO13S1, Coniochaeta endophytica 55S2, Fusarium lateritium 61S2, Aureobasidium microstictum 7F2, Chaetomium globosum 2S1 and Ch. globosum 3L2 were selected for greenhouse tests. Further, Co. endophytica 55S2 and F. lateritium 61S2 could solubilize inorganic phosphate. All isolates except Ch. globosum 3L2 exhibited cellulase activity, while chitinase activity was observed in Ch. globosum 2S1, Ch. globosum 3L2, and F. lateritium 61S2. Finally, Co. endophytica 55S2 and Ch. globosum 2S1 completely controlled the disease on the apple seedling leaves under greenhouse conditions.